Ropewick Application to Control Old World Bluestems - K. R. Harmoney (Kansas Agricultural Experiment Station Research Reports, 2016)
Old world bluestems (OWB) were introduced into the United States in the early 1900s for conservation and forage purposes. The two main OWB species found throughout the southern Great Plains are Caucasian bluestem (Bothriochloa bladhii) and yellow or King Ranch bluestem (Bothriochloa ischaemum). These introduced OWB grasses are warm-season grasses with excellent persistence and production characteristics for regions with low rainfall. These grasses also produce abundant seed and establish more easily under arid conditions compared to some of our most common native warm-season grasses of the Great Plains. The characteristics that enable OWB to be well adapted and to grow and persist in the Great Plains also enable OWB to become invasive and encroach areas where it is not wanted. Several studies have examined herbicides to control OWB, and glyphosate products showed the most economical and promising short-term control success. However, glyphosate is a non-selective herbicide and has the potential to injure almost all vegetation with which it comes into contact, including desirable native species that may be growing among a stand of sprayed OWB. Wick applicators have been used extensively in grain row crop systems to wipe herbicide on weedy species that grow taller than the desirable grain crop. Because OWB matures more quickly than many native species, OWB could potentially be treated with a wick applicator as it matures following its elongation and elevation above native grass species. Therefore, applying glyphosate with a ropewick applicator to control OWB warranted investigation.
Keywords: weed science